A Study to Evaluate Subclinical Muscle Strength Decrease and Quality of Life among Diabetes Individuals (Indian Journal of Public Health Research & Development, 2020)
Background : Diabetes mellitus is a metabolic disorder of multiple aetiologies characterized by chronichyperglycemia resulting from defects in insulin secretion or insulin action. Muscle strength is influencedby insulin resistance, through higher plasma levels, and lipid content in the muscle, therefore it could be amarker for impaired skeletal muscle. These structural and functional changes in the skeletal muscle causedby defective insulin action could be associated with muscle weakness and reduced endurance capacity.This study evaluates the subclinical changes in muscle strength in diabetes and its functional performancecomparing with age-matched healthy subjects.Methods: This observational study totally includes 80 male and female individuals, 40 of type 2 DM andanother 40 of age matched healthy individuals without any difficulty in Activities of daily living wererecruited above 60 years of age, and assessed with HHD and functional measure (FTSTS) and quality of lifemeasure (SF 36) used.Results: Independent sample T test and Pearson correlation coefficient was used to analyze the differenceand correlate among lower extremity muscle strength, FTSTS, and SF 36 in diabetic and healthy individuals;the data obtained were statistically significant, except SF 36 emotional limitation and physical limitationfactor were non-significant. Pearson’s coefficient found to have weak negative correlation in SF 36 andmuscle strength.Conclusion: Type 2 diabetes mellitus has correlated with reduction in muscle strength particularly in lowerlimb which remains subtle and unidentified as the disease progresses the muscle weakness may becomeprogressive and lead to immobilit